2010
DOI: 10.1590/s1806-37132010001400006
|View full text |Cite
|
Sign up to set email alerts
|

Ronco: critérios diagnósticos e tratamento

Abstract: ResumoO ronco é um problema importante com consequentes manifestações sociais e médicas. O passo inicial consiste em confirmar a presença do ronco e excluir qualquer doença respiratória noturna para que o tratamento adequado seja instituído. Este capítulo analisa o gerenciamento atual do ronco e seu tratamento.Descritores: Ronco/diagnóstico; Ronco/cirurgia; Ronco/terapia. AbstractSnoring is a significant problem with social and medical manifestations. After snoring has been confirmed, other nocturnal respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In addition to the individual characteristics that are associated with sleep disorder, some habits and pathologies that were studied in this sample also appear as aggravating factors of the phenomenon, corroborating data from the literature (2) . Risk factors for the syndrome include alcohol and tobacco consumption (18) . In the studied sample, it is observed that these were significantly associated with a greater impairment of the sleep disorder, while, conversely, non-alcoholic and non-smokers were significantly related to the diagnosis of RERAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the individual characteristics that are associated with sleep disorder, some habits and pathologies that were studied in this sample also appear as aggravating factors of the phenomenon, corroborating data from the literature (2) . Risk factors for the syndrome include alcohol and tobacco consumption (18) . In the studied sample, it is observed that these were significantly associated with a greater impairment of the sleep disorder, while, conversely, non-alcoholic and non-smokers were significantly related to the diagnosis of RERAs.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking causes chronic irritation and potentially irreversible inflammation in the airways, and thus, anatomical and physiological changes in the properties of the respiratory tract, affecting airflow. While alcoholism is associated as a predisposing etiological factor of sleep disorders due to the hypotonicity effect of the musculature that can cause (18) . As for the research participants with SAH, these were associated with the severe outcome, corroborating other findings (19) , because snoring is accompanied by a potent inspiratory effort against a semi-fluid pharynx, with large variations in pleural pressure affecting cardiac load (20) .…”
Section: Discussionmentioning
confidence: 99%
“…(PSG) is the gold pattern method to diagnose the OSAHS, even if is clinically evident, only can be confirmed by PSG 24,25 . The polyssonography is a quantitative and specific exam, which consists in continuous monitoring the physiologic variables, such as electroencephalogram, eye movements, thoracoabdominal, air flow and the tone of the submental muscles, aiming to characterize the quantity and quality of sleep 20 .…”
Section: Diagnosementioning
confidence: 99%
“…8 Os efeitos e consequências da AS incluem ronco, 9 sonolência excessiva diurna, aumento da pressão arterial, 10 alterações cognitivas, 11 alterações…”
Section: Introductionunclassified